The Relationship Between Talent Management Practices and Organisational Competitiveness in South African Law Firms - Mbuqe, Sinomtha (University of the Witwatersrand, Johannesburg, 2023)
The globalisation of legal services has massively amplified competition among professional service firms in South Africa and globally. To compete more effectively in the present-day environment, characterized by increased competition and enhanced customer expectations, sustaining high performance is critical. Due to scarcity of talent, law firms compete for the same pool of human resources to acquire and retain to increase growth in profitability and service. Literature has identified talent management practices (“TMP”) such as talent identification, selection, retention, and development as sources of sustainable competitive advantage. Despite talent management and its practices being established concepts in literature and in practice, there is an apparent lacuna in research on TMP in the context of South African law firms and whether such practices enhance their competitiveness. The objective of this study was to ascertain the relationship between TMP and organisational competitiveness in South African law firms operating within the Gauteng province. A quantitative study was undertaken, with statistics gathered from employees of law firms located in Gauteng, South Africa. A random sampling technique was used and data was collected from 56 participants using a semi-structured survey questionnaire. Quantitative data was analyzed using the Statistical Package for Social Sciences (SPSS) to generate descriptive and inferential statistics. The empirical findings indicated that all constructs associated with TMP, namely talent attraction, talent development, talent retention and reasons for using these practices, were positively correlated with organisational competitiveness. However, statistically, talent development increased an organisations competitiveness. The findings thus indicate that talent attraction, talent development and talent retention are important and have an impact on organisational competitiveness. These findings will enable law firms to apply talent development towards continuous organisational competitiveness, which further aids the sustainability of the organisation
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Talent management; Talent Attraction; Talent Development; Talent Retention; Competitiveness; Organisational Performance; Law Firms; UCTD; SDG-8: Decent work and economic growth